2021
DOI: 10.1038/s41372-021-01054-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of patent ductus arteriosus management with neonatal AKI

Abstract: Objective: Investigate relationship between management of patent ductus arteriosus (PDA) and acute kidney injury (AKI) in very low birthweight neonates. Study Design: Retrospective cohort study of neonates, <1500g, admitted to 24 NICUs, 1/1/14 – 3/31/14. AKI diagnosed using the neonatal modified KDIGO definition; diagnosis and treatment of PDA extracted from the medical record. Demographics, clinical characteristics, and AKI stage compared using chi-square and analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Patent ductus arteriosus (PDA) is an important clinical issue for preterm infants and is associated with a higher risk of AKI. 28,29 PDA represents a clinical challenge as AKI may result if it is left untreated; however, classic PDA therapies may also be associated with AKI. While NSAID treatment of PDA added an additional risk for mild AKI, severe AKI was less likely when NSAID treatment was effective.…”
Section: Preterm Neonatesmentioning
confidence: 99%
“…Patent ductus arteriosus (PDA) is an important clinical issue for preterm infants and is associated with a higher risk of AKI. 28,29 PDA represents a clinical challenge as AKI may result if it is left untreated; however, classic PDA therapies may also be associated with AKI. While NSAID treatment of PDA added an additional risk for mild AKI, severe AKI was less likely when NSAID treatment was effective.…”
Section: Preterm Neonatesmentioning
confidence: 99%
“…This is supported by findings demonstrating lower renal oxygen saturation (Rsat) values among extremely premature infants with hsPDA [8]. A recent study demonstrated that infants diagnosed with PDA had higher maximum creatinine concentrations and a three-fold higher risk of developing AKI [9].…”
Section: Introductionmentioning
confidence: 80%
“…8 A recent study demonstrated that infants diagnosed with PDA had higher maximum creatinine concentrations and a three-fold higher risk of developing AKI. 9 Identifying AKI in neonates remains challenging. One of the most commonly utilized definitions is the neonatal modified Kidney Disease Improving Global Outcomes (KDIGO) criteria.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by ndings demonstrating lower renal saturation (Rsat) values among extremely premature infants with hsPDA 8 . A recent study demonstrated infants diagnosed with PDA had higher maximum creatinine concentrations and had a three-fold higher risk to develop AKI 9 .…”
Section: Introductionmentioning
confidence: 99%